CURRENT STATUS OF IFORMATION TECHNOLOGY APPLICATION IN HOSPITAL MANAGEMENT AT HOSPITALS IN THAI BINH PROVINCE IN 2025 (Vietnam Journal of Community Medicine, 2026)
Objective: To assess the current status of information technology (IT) in hospital management at hospitals in Thai Binh province in 2025.Subjects and methods: A cross-sectional descriptive study was conducted among 2,250 participants, at 30 hospitals in Thai Binh province in 2025.Results: Most healthcare workers reported that electronic medical records (EMRs) help reduce medical errors and improve patient safety (85.6%), decrease administrative procedures (96.7%), and facilitate comprehensive and convenient data storage and retrieval (94.4%). Overall, 73.4% of healthcare facilities had successfully implemented EMRs, while 22.2% were in the process of implementation; Additionally 88.9% of healthcare workers had received IT training. Hospital Information Systems (HIS) were the most commonly used software (86.5%). Nearly all healthcare workers considered IT to be very important (99.8%); 96.9% used IT daily, 94% were satisfied, and 99.2% perceived it as effective. Major challenges included non-uniform IT infrastructure across hospitals (75.6%), outdated networks or inappropriate system design (62.2%), limited IT skills among healthcare workers (75.6%) and unstable network connectivity (64.7%). From the patient perspective, most patients experienced waiting times of less than 15 minutes for administrative procedures (83.4%) and less than 15 minutes for medical consultation (54.5%), with corresponding satisfaction rates of  87% and 83.1%. Waiting times for laboratory test results of ≤ 2 hours accounted for 94.2%, with 73.6% of patients reporting satisfaction. Overall, 78.2% of patients perceived a marked or very marked improvement in healthcare service quality associated with IT application.Conclusion: The application of information technology in hospital management has been widely implemented, improving management efficiency, reducing administrative procedures, and increacing satisfaction among healthcare workers and patients.
Keywords: Application of information technology; Hospital management.